Performance Analysis of Non-uniform Filter Bank with Equi ripple Band pass Filter (International Journal of Engineering and Computer Science, 2016)
In this paper we present a non-uniform filter bank (NUFB) matched to a given signal. To obtain matched M-channel NUFB, first, we choose the decimation set having M-down sampling/decimation factors for which perfect reconstruction NUFB exist and then using novel approach proposed in this paper, M-channel signal matched analysis bank is estimated. The outputs of all filters at the analysis side of proposed filter bank are mutually as well as across various channels are uncorrelated. By using well established theory of multirate filter bank, M-channel NUFB matched to signal is obtained. The equiripple band pass filter will provide better tradeoff compared to previous non uniform Filter bank obtained in this fashion will be useful to compress code or represent the signal or image in the best possible manner.